If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 1 = 12x + 29 Reorder the terms: 1 + 3x = 12x + 29 Reorder the terms: 1 + 3x = 29 + 12x Solving 1 + 3x = 29 + 12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12x' to each side of the equation. 1 + 3x + -12x = 29 + 12x + -12x Combine like terms: 3x + -12x = -9x 1 + -9x = 29 + 12x + -12x Combine like terms: 12x + -12x = 0 1 + -9x = 29 + 0 1 + -9x = 29 Add '-1' to each side of the equation. 1 + -1 + -9x = 29 + -1 Combine like terms: 1 + -1 = 0 0 + -9x = 29 + -1 -9x = 29 + -1 Combine like terms: 29 + -1 = 28 -9x = 28 Divide each side by '-9'. x = -3.111111111 Simplifying x = -3.111111111
| 6x-3=37-4x | | 3.14x4/3= | | -8+5c=6c | | 19-3j=7 | | 12x-8=62-2x | | z^2-7z= | | -2-4p=-7-5p | | -50.00+50x=300 | | (-9m+9)+(8m+8)= | | -q-5=4q | | -4-3m=19 | | (z-7)(z-7)= | | 5x-8=11+7x-2x | | (z-7)(z-7)=0 | | 2-27n=0 | | X+(x+2)+(x+4)=-15 | | 5x-8=11+7x-2 | | 0.75x+25=250.00 | | (X+1)(8x)=a | | 2(3x-3)=3(2x+2) | | 5y=-1x-3 | | r=2t+3 | | 8x=16+27 | | 2*(3x-8)+14=16 | | x*20/100=158 | | 2(3x-8)+14=16 | | x/6--1/x=1/3 | | x-20.7=9.5forx | | -8v=-9v+2 | | 7x-11=2(1-x) | | 3n+2n-4n= | | 20x-y=60 |